General Theoretical Notions About the Semiotics of Culture and the Arts - Montero Zayas, Geovannys; Prado Soriano, Leandro Ernesto; Obloberdiyevn, Djamaldinova Shakhlo; Akimjaková, Beáta; Pavlíková, Martina (Journal of Education Culture and Society, 2025)
Aim. This article offers an approach to general theoretical issues in the semiotics of culture and the arts, with an emphasis on key concepts from these areas of knowledge. The evolution of the object of study, theoretical discussions associated with different theoretical and methodological traditions, and the basic categorical system are among the topics covered. Methods. To prepare the article, general or theoretical methods were used, such as analytical-synthetic and inductive-deductive, which were materialized through documentary analysis, interpretation, and the study and criticism of sources. Results. This article adopts positions regarding categories and concepts of semiotics, such as culture, languages, the semiotic transposition of languages, codes, text, and criteria of textuality. It analyzes definitions and theoretical proposals from various authors and offers valuable criteria for continuing the scientific debate. Conclusions. Semiotics is an area of human knowledge characterized by a multiplicity of theoretical and methodological approaches and positions. In many scientific and academic practices, there is still an attachment to the founding notions of Peirce and Saussure, as well as to the traditional designations of semiotics and semiology, or to the dichotomous and trichotomous conceptions of the sign, aspects that are too rudimentary to satisfy current demands for the semiotics of culture and the arts. Cognitive value. The article provides a solidly argued study, based on an extensive bibliographic review, knowledge of cultural and artistic issues, and the practice of art itself in different manifestations.